Detection of HPV in mouth floor squamous cell carcinoma and its correlation with clinicopathologic variables, risk factors and survival - Simonato, L. E. [UNESP]; Garcia, J. F. [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Mattar, N. J.; Veronese, L. A. [UNESP]; Miyahara, Glauco Issamu [UNESP] (Wiley-Blackwell, 2008)
The human papillomavirus (HPV) has been historically associated with head and neck cancers, although its role in oral carcinogenesis remains poorly defined. The purpose of this study was to investigate the prevalence of HPV in mouth floor squamous cell carcinoma and correlate it with clinicopathologic variables, risk factors and survival. HPV presence was evaluated by nested polymerase chain reaction (nPCR) in 29 paraffin-embedded specimens of mouth floor squamous cell carcinoma. HPV DNA was detected in 17.2% (5 of 29) of the specimens; the highest prevalence was observed in non-smoking patients over the age of 60 years. All HPV DNA positive specimens were detected in men with clinical stage III and IV lesions, being most of which were moderately differentiated. Despite this correlation there were no statistically significant differences observed among the analyzed variables, including patients' survival. The relatively low incidence of HPV DNA present in these tumors suggests that this virus does not, by itself, have a significant role in the development of mouth floor squamous cell carcinoma. J Oral Pathol Med (2008) 37: 593-598
Keywords: human papillomavirus; polymerase chain reaction; squamous cell carcinoma